Mitochondrial Sirtuin TcSir2rp3 Affects TcSODA Activity and Oxidative Stress Response in Trypanosoma cruzi - dos Santos Moura, Leila; Santana Nunes, Vinícius; Gomes, Antoniel A. S. [UNESP]; Sousa, Ana Caroline de Castro Nascimento; Fontes, Marcos R. M. [UNESP]; Schenkman, Sergio; Moretti, Nilmar Silvio (Frontiers, 2021)
Trypanosoma cruzi faces a variety of environmental scenarios during its life cycle, which include changes in the redox environment that requires a fine regulation of a complex antioxidant arsenal of enzymes. Reversible posttranslational modifications, as lysine acetylation, are a fast and economical way for cells to react to environmental conditions. Recently, we found that the main antioxidant enzymes, including the mitochondrial superoxide dismutase A (TcSODA) are acetylated in T. cruzi, suggesting that protein acetylation could participate in the oxidative stress response in T. cruzi. Therefore, we investigated whether mitochondrial lysine deacetylase TcSir2rp3 was involved in the activity control of TcSODA. We observed an increased resistance to hydrogen peroxide and menadione in parasites overexpressing TcSir2rp3. Increased resistance was also found for benznidazole and nifurtimox, known to induce reactive oxidative and nitrosactive species in the parasite, associated to that a reduction in the ROS levels was observed. To better understand the way TcSir2rp3 could contributes to oxidative stress response, we analyzed the expression of TcSODA in the TcSir2rp3 overexpressing parasites and did not detect any increase in protein levels of this enzyme. However, we found that these parasites presented higher levels of superoxide dismutase activity, and also that TcSir2rp3 and TcSODA interacts in vivo. Knowing that TcSODA is acetylated at lysine residues K44 and K97, and that K97 is located at a similar region in the protein structure as K68 in human manganese superoxide dismutase (MnSOD), responsible for regulating MnSOD activity, we generated mutated versions of TcSODA at K44 and K97 and found that replacing K97 by glutamine, which mimics an acetylated lysine, negatively affects the enzyme activity in vitro. By using molecular dynamics approaches, we revealed that acetylation of K97 induces specific conformational changes in TcSODA with respect to hydrogen-bonding pattern to neighbor residues, suggesting a key participation of this residue to modulate the affinity to (Formula presented.). Taken together, our results showed for the first time the involvement of lysine acetylation in the maintenance of homeostatic redox state in trypanosomatids, contributing to the understanding of mechanisms used by T. cruzi to progress during the infection.
Keywords: acetylation; oxidative stress; sirtuins; superoxide dismutase; Trypanosoma cruzi